2021
DOI: 10.1021/acs.nanolett.1c02493
|View full text |Cite
|
Sign up to set email alerts
|

Even–Odd Layer-Dependent Anomalous Hall Effect in Topological Magnet MnBi2Te4 Thin Films

Abstract: Recently, MnBi 2 Te 4 has been demonstrated to be an intrinsic magnetic topological insulator and the quantum anomalous Hall (QAH) effect was observed in exfoliated MnBi 2 Te 4 flakes. Here, we used molecular beam epitaxy (MBE) to grow MnBi 2 Te 4 films with thickness down to 1 septuple layer (SL) and performed thickness-dependent transport measurements. We observed a nonsquare hysteresis loop in the antiferromagnetic state for films with thickness greater than 2 SL. The hysteresis loop can be separated into t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
78
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 45 publications
(85 reference statements)
8
78
0
1
Order By: Relevance
“…Similarly, the surface term also increases, albeit less dramatically. For Te capped samples R xy , F increases for reduced thickness, [ 48 ] and suggests the sample's effective magnetic thicknesses becomes thinner, agreeing with the above results of the MR. H C is nominally the same for both components and exhibits a small increase for times up to 40 min. Surprisingly, at ≈40–60 min there emerges an additional component with negative amplitude, R xy , F3 .…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Similarly, the surface term also increases, albeit less dramatically. For Te capped samples R xy , F increases for reduced thickness, [ 48 ] and suggests the sample's effective magnetic thicknesses becomes thinner, agreeing with the above results of the MR. H C is nominally the same for both components and exhibits a small increase for times up to 40 min. Surprisingly, at ≈40–60 min there emerges an additional component with negative amplitude, R xy , F3 .…”
Section: Resultssupporting
confidence: 76%
“…For finite thickness MnBi 2 Te 4 it has been empirically found that the hysteretic loops of the anomalous Hall effect can be decomposed into multiple individual loops. [ 48 ] Specifically, this can be quantified by fitting the data to a function of the form: Rxy,A(H)badbreak=iRxy,Fitanhwi(Hbadbreak−HC,i)\[ \begin{array}{*{20}{c}}{{R_{xy,A}}\left( H \right) = \mathop \sum \limits_i {R_{xy,Fi}}\tanh {w_i}\left( {H - {H_{C,i}}} \right)}\end{array} \] where i indexes the individual anomalous Hall component, which is found to be either 2 or 3 in this work, R xy , Fi is the magnitude of the response, w i is the width of the transition, and H C , i is the coercive field (where the anomalous Hall component vanishes). The hyperbolic tangent function is derived from a Langevin‐type analysis for the net magnetization in a magnetic field.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…surface collapse and reconstruction 12 , temperature-independent bandgap 1,13 and even the gapless surface Dirac cone 14 , revealed that magnetic and topological properties of MBT are sensitive to the surface structure. Inevitable Mn-doped Bi2Te 3 phase exists in the MBT, which originates from the Te vacancy 12 or the FM island on some areas 15 , can induce the magnetic moment at the surface 13 and weaken the interaction between magnetism and topological surface state.…”
Section: Introductionmentioning
confidence: 99%